2016
DOI: 10.3390/ma9030160
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Microspherical Silver-Reduced Graphene Oxide-Bismuth Vanadate Composite and Evaluation of Its Photocatalytic Activity

Abstract: A novel Ag-reduced graphene oxide (rGO)-bismuth vanadate (BiVO4) (AgGB) ternary composite was successfully synthesized via a one-step method. The prepared composite was characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), energy dispersive X-ray (EDX), Brunauer-Emmett-Teller (BET) surface area measurement, Raman scattering spectroscopy, and ultraviolet-visible diffuse-reflection spectroscopy (UV-vis DRS). The results showed that bulk monoclinic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…The photogenerated electrons can react with dissolved oxygen molecules (O 2 ) to yield superoxide radical anions (·O 2 − ), as shown in (20), and ·O 2 − can react with H 2 O to produce ·OH (21) [55,56]. As previously mentioned, the VB of BiVO 4 can oxidize OH − to ·OH (22), and h + , ·O 2 − , and ·OH are strong oxidizing agents for the decomposition of organic dyes (23) [57]. The whole set of redox reactions can be summarized as follows: BiVO4/Bi2S3+RhB adsorption RhB+ normalhsans-serifνRhB* RhB* +BiVO4/Bi2S3 BiVO4/Bi2S3 (e)+ RhB+ Bi2S3+ normalhsans-serifνBi2S3 (h+)+ Bi2S3 (e) BiVO4+ normalhsans-serifν BiVO4 (h+)+ BiVO4 (e) Bi2S3 (e) + BiVO4BiVO4 (e) BiVO4…”
Section: Resultsmentioning
confidence: 99%
“…The photogenerated electrons can react with dissolved oxygen molecules (O 2 ) to yield superoxide radical anions (·O 2 − ), as shown in (20), and ·O 2 − can react with H 2 O to produce ·OH (21) [55,56]. As previously mentioned, the VB of BiVO 4 can oxidize OH − to ·OH (22), and h + , ·O 2 − , and ·OH are strong oxidizing agents for the decomposition of organic dyes (23) [57]. The whole set of redox reactions can be summarized as follows: BiVO4/Bi2S3+RhB adsorption RhB+ normalhsans-serifνRhB* RhB* +BiVO4/Bi2S3 BiVO4/Bi2S3 (e)+ RhB+ Bi2S3+ normalhsans-serifνBi2S3 (h+)+ Bi2S3 (e) BiVO4+ normalhsans-serifν BiVO4 (h+)+ BiVO4 (e) Bi2S3 (e) + BiVO4BiVO4 (e) BiVO4…”
Section: Resultsmentioning
confidence: 99%
“…The photocatalytic activity of a catalyst is determined by its capacity to absorb sunlight and separate excited electron–hole pairs . Many studies have reported the basic process of this photocatalytic reaction . To prove the formation process of radicals during the photocatalytic reaction in this study, ESR analysis was employed to detect • OH and • O 2 − radicals under NIR irradiation.…”
Section: Resultsmentioning
confidence: 98%
“…Nickel doped Bi 2 S 3 has also been applied in the degradation of congo red and rose bengal dyes by visible light illumination with successful results [40]. A nanocomposite consisting of BiVO 4 , Ag and reduced graphene oxide (rGO) was also synthesised and used to degrade rhodamine B dye [41]. They identified the composite to possess more photocatalytic reaction sites because of enhanced charge carriers separation ability of the BiVO 4 , electron transfer property of the silver nanoparticles and surface plasmon effect.…”
Section: Degradation Of Textile Dyesmentioning
confidence: 99%